2020
DOI: 10.1101/2020.03.28.013169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imperative role of particulate matter in innate immunity during RNA virus infection

Abstract: 25Sensing of pathogens by specialized receptors is the hallmark of the innate immune response. 26Innate immune response also mounts a defense response against various allergens and pollutants 27 including particulate matter present in the atmosphere. Air pollution has been included as the top 28 threat to global health declared by WHO which aims to cover more than three billion people against 29 health emergencies from 2019-2023. Particulate matter (PM), one of the major components of air 30 pollution, is a si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Similarly, PM 2.5 levels were much lower than the EPA 24-hour standard of 35 µg/m 3 based on the three-year average of the annual 98th percentile concentrations [43]. However, we were curious to examine the effects of these low PM 2.5 levels, because a recent non-peer reviewed preprint reported that exposure to PM 10 could significantly enhance RNA virus infection such as N.D.V., H1N1 (PR-8), and H5N1 in human lung epithelial A459 cells [44] by increasing viral replications. Temperature levels were gradually increasing during the observation period (Figure 4B) but were mostly observed between 30 and 50 • F. This early spring temperature range was slightly higher than the last year (when March first week's data were compared), but it was still below 70 • F at which viral lipid-dependent attachment to host cells [45] could be facilitated [46].…”
Section: Descriptive Analysis Of Data On Covid-19 Cases and Deaths Ozone Pm25 And Meteorological Factorsmentioning
confidence: 99%
“…Similarly, PM 2.5 levels were much lower than the EPA 24-hour standard of 35 µg/m 3 based on the three-year average of the annual 98th percentile concentrations [43]. However, we were curious to examine the effects of these low PM 2.5 levels, because a recent non-peer reviewed preprint reported that exposure to PM 10 could significantly enhance RNA virus infection such as N.D.V., H1N1 (PR-8), and H5N1 in human lung epithelial A459 cells [44] by increasing viral replications. Temperature levels were gradually increasing during the observation period (Figure 4B) but were mostly observed between 30 and 50 • F. This early spring temperature range was slightly higher than the last year (when March first week's data were compared), but it was still below 70 • F at which viral lipid-dependent attachment to host cells [45] could be facilitated [46].…”
Section: Descriptive Analysis Of Data On Covid-19 Cases and Deaths Ozone Pm25 And Meteorological Factorsmentioning
confidence: 99%
“…Studies have shown that alveolar macrophages from people living in highly polluted cities have a reduced innate immune capacity, which is proportional to the amount of phagocytosed PM ( 20 ). Experimental studies in mice have found that PM exposure reduces activity at the interferon (INF)-β gene promoter, and subsequent INF-β transcription, and enchanted influenza replication ( 37 ). As innate immunity, in general, and in particular INF-β, a key antiviral cytokine, is reduced by PM, it is likely that these mechanisms would enhance SARS-CoV-2 pathogenicity.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…to occur through different mechanisms; in this study, we explore the following hypotheses: 1) PM has been suggested to facilitate viruses transmission, due to 15 its role in shielding the virus during airborne transport [5,6,7,8,9]; 2) The long-term exposure, particularly to CO and NO 2 , increases the susceptibility of a population to adverse health conditions [10,11]; 3) PM levels are associated 2 All rights reserved. No reuse allowed without permission.…”
Section: Statistical Links Between Air Quality and Covid-19 Daily Casmentioning
confidence: 99%
“…Statistical links between air quality and COVID-19 daily cases are expected to occur through different mechanisms; in this study, we explore the following hypotheses: 1) PM has been suggested to facilitate viruses transmission, due to its role in shielding the virus during airborne transport [5, 6, 7, 8, 9]; 2) The long-term exposure, particularly to CO and NO 2 , increases the susceptibility of a population to adverse health conditions [10, 11]; 3) PM levels are associated with urban mobility [12], thus we expect them to respond to the effectiveness of local social distancing measures. In the following subsections we discuss in detail these mechanisms as well as the statistical techniques employed to explore them.…”
Section: Introductionmentioning
confidence: 99%